About Asia e University - Asia e University, AeU (2015)
Asia e University (AeU) is a collaborative multinational university initiated by the Asia Cooperation Dialogue (ACD), a body established in 2002 to promote Asian cooperation at a continental level. Established as a Malaysian initiative, to be the prime mover of e-Education, it is supported by 34 ACD Member Countries as affirmed at the ACD Ministerial Meetings held in Islamabad in 2005 and Doha in 2006.